2002
DOI: 10.1053/ejvs.2001.1545
|View full text |Cite
|
Sign up to set email alerts
|

Three Cases of Hyperperfusion Syndrome Identified by Daily Transcranial Doppler Investigation After Carotid Surgery

Abstract: daily TCD investigation in all patients undergoing CEA seems an effective strategy for the presymptomatic detection of HS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 16 publications
0
12
1
1
Order By: Relevance
“…In previous studies using TCD, the diagnostic criterion of hyperperfusion syndrome was mostly a Ն2-fold increase in MCA peak systolic or MFV after CEA. 3,4,6 In this study, an MFV ratio of Ն1.5 within 4 postsurgical days yielded a sensitivity of 100% and a specificity of 84%. An MFV ratio of Ն1.4 the next morning after CEA was another indicator that predicted hyperperfusion syndrome perfectly, although its specificity was relatively low (67%).…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…In previous studies using TCD, the diagnostic criterion of hyperperfusion syndrome was mostly a Ն2-fold increase in MCA peak systolic or MFV after CEA. 3,4,6 In this study, an MFV ratio of Ն1.5 within 4 postsurgical days yielded a sensitivity of 100% and a specificity of 84%. An MFV ratio of Ն1.4 the next morning after CEA was another indicator that predicted hyperperfusion syndrome perfectly, although its specificity was relatively low (67%).…”
Section: Discussionmentioning
confidence: 50%
“…[3][4][5][6] However, because of questions regarding accuracy of TCD in diagnosing hyperperfusion syndrome, some controversy remained. Because precise placement of the sample volume as well as angle correlation is not possible by means of the TCD technique, TCD cannot determine absolute MCA flow velocity values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, in acute hypertensive encephalopathy, there is failure of autoregulatory vasoconstriction with dilation of distal vessels and increased cerebral blood flow (30); fibrinoid necrosis of arterioles leads to cerebral microinfarcts and petechial hemorrhages (3). Second, the cerebral hyperperfusion syndrome may follow cerebral revascularisation by endarterectomy (24) or stent placement (19); newly elevated perfusion pressure overwhelms arteriolar autoregulation, sometimes precipitating intracerebral hemorrhage. Finally, a breakdown of cerebral autoregulation with hyperperfusion may lead to vasogenic cerebral edema in the preeclampsia/eclampsia syndrome (33).…”
Section: Discussionmentioning
confidence: 99%
“…Schaafsma et al (2002) suggested that a blood-flow velocity level of the postoperative ipsilateral middle cerebral artery exceeding the preoperative level by 100% would be an early and sensitive indicator of the occurrence of hyperperfusion syndrome. Thirteen patients in this study showed perioperative transition perfusion, and they all had a high stenosis situation.…”
Section: Discussionmentioning
confidence: 99%